2019
DOI: 10.1017/s037346331900081x
|View full text |Cite
|
Sign up to set email alerts
|

A Mutual Information-Based Bayesian Network Model for Consequence Estimation of Navigational Accidents in the Yangtze River

Abstract: Navigational accidents (collisions and groundings) account for approximately 85% of mari-time accidents, and consequence estimation for such accidents is essential for both emergency resource allocation when such accidents occur and for risk management in the framework of a formal safety assessment. As the traditional Bayesian network requires expert judgement to develop the graphical structure, this paper proposes a mutual information-based Bayesian network method to reduce the requirement for expert judgemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In binary LR, the binary dependent variable comprises two categories which are generally represented as 0 and 1. On the other hand, more than two categories of dependent variables are handled in multinomial LR (Sapri et al, 2017; Wu et al, 2020). In this study, two levels of accident severity (the dependent variable) were taken into consideration: serious or non-serious.…”
Section: Methodsmentioning
confidence: 99%
“…In binary LR, the binary dependent variable comprises two categories which are generally represented as 0 and 1. On the other hand, more than two categories of dependent variables are handled in multinomial LR (Sapri et al, 2017; Wu et al, 2020). In this study, two levels of accident severity (the dependent variable) were taken into consideration: serious or non-serious.…”
Section: Methodsmentioning
confidence: 99%
“…Also, they showed that mutual information outperforms Wrapper methods in variable selection when the number of variables is large. The merit of mutual information is to avoid unnecessary work and reduce the need for expert judgment, provide a straightforward, fast, with relatively low computational complexity, and costeffective approach to recognize the influencing macroeconomic variables on port throughput (Wu et al, 2020;Yang et al, 2018). Mutual information also offers a useful visual tool for a better understanding of the dependencies among variables (Li et al, 2009).…”
Section: Mutual Information Analysismentioning
confidence: 99%
“…Qualitative (or expert-judgment-based) evaluation of influencing factors on port throughput may be time consuming, laborious, include biases (Wu et al, 2020) and rely on incomplete and subjective knowledge, which is conditional on the background and experience of experts (Hänninen, 2014). Furthermore, experts are not always available to determine the influencing variables (Montewka et al, 2014).…”
Section: Identification Of the Relation Between Port Throughput And Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bayesian network (BN) is a graphical network of probabilistic reasoning, and it can analyze the uncertain relationship between variables in a complex network [ 17 ]. This method is widely used in risk analysis [ 18 , 19 , 20 , 21 ], risk assessment [ 22 , 23 , 24 , 25 ] and decision-making [ 26 , 27 ]. Zhu et al constructed a BN model of chemical terrorist attacks to conduct risk analysis, which provided theoretical support for the security prevention work of the risk management department [ 28 ].…”
Section: Introductionmentioning
confidence: 99%